What a neurologist should know about PET and SPECT functional imaging for parkinsonism: A practical perspective. (February 2019) - Thobois, Stéphane; Prange, Stéphane; Scheiber, Christian; Broussolle, Emmanuel
Abstract: The diagnosis of a parkinsonian syndrome based on clinical criteria remains sometimes difficult, especially at disease onset. Brain or heart molecular imaging techniques (SPECT or PET) can provide a major help to improve and speed up diagnosis, influencing treatment strategies. Presynaptic dopaminergic imaging using either [ 18 F]-Dopa PET or 123 I -2β-Carbomethoxy-3β-(4-Iodophenyl)- N-(3-Fluoropropyl) Nortropane ([ 123 I]-Ioflupane)SPECT demonstrates or rules out the presence of a dopaminergic degenerative process. This allows to distinguish Parkinson's disease, Parkinson "plus" syndromes and dementia with Lewy bodies (reduced radiotracers binding) from essential tremor, psychogenic, post-neuroleptic or vascular parkinsonisms, dopa-responsive dystonia and Alzheimer's disease (normal radiotracers binding). For differential diagnosis between Parkinson's disease and Parkinson "plus" syndromes, brain molecular imaging with [ 18 F]-Fluorodeoxyglucose ([ 18 F]-FDG) PET or 99m Tc-HMPAO SPECT can provide useful information, whereas [ 18 F]-Dopa PET or [ 123 I]-Ioflupane does not separate these entities. Finally, sympathetic cardiac [ 123 I]-Metaiodobenzylguanidine ([ 123 I]-MIBG) scintigraphy or SPECT can help distinguishing Parkinson's disease and dementia with Lew bodies (decreased binding) from multiple system atrophy and progressive supranuclear palsy (normal binding). New radiotracers notably those targeting the pathological process itself such as Tau aggregates are under development and may provide interesting informations to delineate the different Parkinson "plus" syndromes. Highlights: [ 18 F]-Dopa PET/[ 123 I]-Ioflupane assesses dopaminergic degeneration. [ 18 F]-Dopa PET/[ 123 I]-Ioflupane SPECT do not distinguish PD from Parkinson "Plus". [ 18 F]-FDG PET separates PD from Parkinson "Plus". [ 123 I]-MIBG SPECT help distinguishing PD and DLB from MSA/PSP.